Handbook of primary care psychology - Haas, Leonard J. (Oxford University Press, 2004)
"Aimed at psychologists and other mental health specialists working in primary care, the Handbook of Primary Care Psychology is a guide to the world of primary care medicine, a primer on a range of critical clinical issues, and a toolbox of accessible clinical resources. Scholarly and at the same time practical, this volume offers both the clinician and the researcher a look at the contexts in which psychological services become of paramount importance to the health of a patient."--Jacket